The relationship between recessions and health - Nick Drydakis (IZA World of Labor, 2021)
Recessions are complex events that affect personal health and behavior via various potentially opposing mechanisms. While recessions are known to have negative effects on mental health and lead to an increase in suicides, it has been proven that they reduce mortality rates. A general health policy agenda in relation to recessions remains ambiguous due to the lack of consistency between different individual- and country-level approaches. However, aggregate regional patterns provide valuable information, and local social planners could use them to design region-specific policy responses to mitigate the negative health effects caused by recessions.
Keywords: I30; I31; I32; I38; 330; recessions; unemployment; mortality; suicides; health; mental health